Systematic review: Soluble immunological biomarkers in advanced non-small-cell lung cancer (NSCLC). (September 2020) - Mildner, Finn; Sopper, Sieghart; Amann, Arno; Pircher, Andreas; Pall, Georg; Köck, Stefan; Naismith, Erin; Wolf, Dominik; Gamerith, Gabriele
Highlights: Liquid Biopsy represents an asset for longitudinal monitoring in cancer. Liquid Biopsy provides valuable information about the tumor immune microenvironment. CtDNA, CTCs, PBMC and soluble proteins are auspicious biomarkers for immunotherapies. Heterogenic trial design and methods complicate the evaluation of clinical relevance. Further data and prospective trials are needed for the clinical implementation. Abstract: In the highly dynamic field of advanced malignancies, biomarkers from liquid samples are urgently needed to improve treatment tailoring. However, the heterogenic data lack direct comparison of assays, vectors and relevant validations are rarely found. Therefore, we classified the available studies based on three categories: Measured vectors, applied technique and detected biomarker. High blood tumor mutational burden and low baseline levels of soluble programmed cell death 1 ligand 1 (PD-L1) appear to predict treatment responses to immunotherapy. A high PD-1 + CD4 + T-cell count was associated with poor overall survival, PD-1 + CD8 + T-cells connect to a favorable outcome. Circulating tumor cells expressing PD-L1 were mainly associated with poor overall survival and treatment failure. Conclusion: Measurement of immunological factors as liquid biomarkers is feasible and has shown promising results. The use of coherent nomenclatures, cross-platform assay comparisons and validations through appropriate powered clinical trials are urgently required to push this auspicious field.